Safety and Tolerability of Both Arm Ischemic Conditioning in Patients With Major Depression: A Proof of Concept Study - Wang, Zuowei; Li, Xujuan; Li, Ningning; Huang, Leping; Liu, Jiawen; Yang, Bixiu; Shi, Jingquan; Fei, Yue; Ji, Xunming; Gao, Keming; Ren, Ming (Frontiers in Psychiatry, 2020)
Purpose: A substantial proportion of patients with major depressive disorder (MDD) does not respond or cannot tolerate to currently available treatments. This study was to assess the safety and tolerability of Remote Limb Ischemic Preconditioning (RLIPC) as an adjunctive therapy in patients with MDD. Patients and methods: Enrolled patients underwent RLIPC, 5 cycles of simultaneous bilateral arm ischemia, 5 minutes and followed by reperfusion of each cycle, and once daily for 8 consecutive weeks. Depression and anxiety severity, and quality of life were assessed every 2 weeks. Descriptive analysis was used for safety and tolerability data. Results: Thirty-seven participants completed at least one RLIPC. Twenty-four of them (64.9%) completed the study. Twelve patients prematurely discontinued the study due to poor adherence, and one due to a mild side effect. The changes in HRSD-17, GAD-7 and QOL-6 total scores from baseline to the endpoint were significant from the end of second week treatment onwards. The responder and remission rates were 59.46% (22/37) and 54.05% (20/37) at the endpoint, respectively. Conclusion: RLIPC was safe and well tolerated, and may be effective in reducing depressive symptoms in patients with MDD. Large studies are warranted to test its efficacy and safety as monotherapy or adjunctive therapy in the treatment of MDD.